Evaluation of video payload over low latency networks: Flexilink. Issue 3 (3rd May 2020) - Ma, Rongxuan; Wang, Yonghao; Hu, Wei; Karalakath, Mahir Payyanil
ABSTRACT: Broadcast organisations need to handle both time deterministic traffic and best effort traffic. The adoption of packet networks allows a single converged network for handling both real-time (RT) media traffic as well as data traffic. Due to the historic pervasive growth of IP network, they are widely used to realise this converged network. However, they do have several drawbacks like big header size, software switching delays and inability to support multiple addressing schemes. To overcome these issues, solutions like traffic engineering, quality of service and over-provisioning are implemented in IP networks but has resulted in higher cost, power and system requirements. Flexilink network has been tested for audio payloads using simulation model and outperforms any existing RT network by providing an exceptional average end-to-end delay of microsecond range and a jitter below the audible threshold for live digital audio streaming. However, it is not tested for video payloads. A review of various networks used RT media distribution is included in this paper. The Flexilink architecture design modification to support the most widely used video formats such as MPEG-TS, MPEG-PS and SDI streams is explained. The average delay for multiple video streams over Flexilink is provided using simulation model. The recommendation for testing Flexilink using hardware is also explained in this paper. The Flexilink Mac design uses dual-buffer system to handle AF (asynchronous flow) and SF (synchronous flow) separately, with the Frame structure that supports current Ethernet frames. GRAPHICAL ABSTRACT: